Analisis Tingkat Kepuasaan SMK terhadap Pendampingan Politeknik Negeri Bali pada Program Smk Pusat Keunggulan - I Gusti Agung Mas Krisna Komala Sari; I Gde Agus Jaya Sadguna; Agus Adi Putrawan; Ni Made Sintya Rani (Syntax Corporation, 2023)
This research aims to analyze the understanding and concern of environmental accounting for medical waste management at the Plawad Karawang Community Health Center. This research method uses qualitative data collection techniques using observation, interviews and documentation. The results of this research are that the Plawad Community Health Center has an understanding and concern for protecting and maintaining the surrounding environment, by minimizing and preventing the negative impact of the waste produced, whether by managing medical waste or being an example for people who visit the Plawad Community Health Center by providing domestic trash cans. or also called household waste (non-medical waste), and medical waste, as well as B3 waste. Plawad Community Health Center has not fully implemented environmental accounting, but the Community Health Center has incurred costs incurred from operational activities related to environmental maintenance.